Entrepreneurship : a practical guide to developing and managing your own business - Udeh, John O. (Jos, Nigeria : Jons and Lors, 1990)
This book provides an insight on how to manage personal business. It will also serve undergraduate students aspiring to be self-employed during and after school.
Includes glossary.
asm 04/03/2019
Loans
Keywords: Enterpreneurship; Nigeria